Overcoming binge eating - Fairburn, Christopher G. (Guilford Press, 1995)
Virtually two books in one, Overcoming Binge Eating provides all the information needed both to understand the problem and bring it under control. Dispelling many of the myths associated with binge eating, Part One provides a comprehensive and up-to-date account of current knowledge about binge eating problems. Chapters address such issues as: * who binges and why? * how binge eating differs from everyday overeating * whether binge eating is an addiction * how binge eating affects people emotionally and physically * the ways those who binge can gain control. Part Two of the book is a new self-help program based on the most effective strategies for binge eating problems. Designed to be used on its own or in conjunction with therapy, the program provides step-by-step guidance for: * overcoming the urge to binge * gaining control of eating behavior * reducing the risk of relapse * establishing stable, healthy eating habits. Comprehensive, accessible, and eminently practical, this important new book offers advice, encouragement, and detailed guidance for anyone who suffers from binge eating problems. It also provides the latest information for those wanting to learn about these problems.